The Potential Analysis of the Pineapple Chips Household Business in Kuala Alam Village - Rismawati Putri; Wan Junita Raflah (Politeknik Kampar, 2024)
Pineapple Fruit Chips is one of the creations of processed pineapple fruit into snacks. This study aims to determine the potential of the pineapple chips business, determine the results of the analysis of the potential of pineapple chips with SWOT analysis and how the strategy optimises the potential to develop the pineapple chips business run by Bumdes Kuala Alam. This research uses descriptive qualitative methods by conducting interviews, and documentation. The data analysis technique uses SWOT analysis, IFAS and EFAS matrix. The results of this study show an IFAS score value of 3.67 which identifies a strong internal position, while the EFAS score value is 3.2 which indicates that pineapple chips respond to existing opportunities and avoid threats in the market. Analysis of the potential of pineapple chips products developed at BUMDes Kuala Alam shows that this product is in a favourable condition, located in quadrant I which indicates growth. Strength factors are more dominant than weaknesses, while the influence of opportunity factors is greater than threats. This conclusion provides a strategic foundation for BUMDes Kuala Alam in developing and marketing pineapple chips products effectively and sustainably.